Perlindungan dan Pertanggungjawaban Hukum Bagi Notaris dan Pejabat Pembuat Akta Tanah Terhadap Keterangan Palsu Para Pihak Dalam Akta (466/PID.B/2023/PN.JKT.SEL) - Sukandar, Dimas Aldriansyah; Tarsono, Edy; Barus, Zulpadli (Jurnal Ilmiah Global Education, 2025)
Land sale transactions often involve the creation of authentic deeds by Land Deed Officials (PPAT) and Notaries, which serve as valid evidence of land rights transfer. However, in practice, false statements by involved parties during the deed-making process frequently occur, potentially harming various stakeholders, including PPAT and Notaries. This study aims to analyze legal protection for PPAT and Notaries against false statements in authentic deed-making, with a case study of Decision Number 466/Pid.B/2023/PN.JKT.SEL. The research employs a normative legal approach by examining relevant legal regulations, legal doctrines, and court decisions. The findings indicate that PPAT and Notaries may bear legal responsibility if proven negligent in verifying the identities and statements of the involved parties. Nevertheless, legal protection for PPAT and Notaries can be enhanced through stricter regulations, improved verification mechanisms, and stronger sanctions for parties providing false statements. The study concludes that stricter supervision of authentic deed-making and increased legal awareness among PPAT and Notaries are necessary to prevent their involvement in document falsification cases